“Ricos e Pobres no Alentejo”: Exploração Laboral e Transformação nas Expectativas dos Trabalhadores Agrícolas Nepaleses em Portugal - Pereira, A. (“Rich and Poor in Alentejo”: Labor Exploitation and Transformation in the Expectations of Nepalese Agricultural Workers in Portugal, 2019)
Starting from a classic anthropological monograph on the distribution of land and social classes in the rural Alentejo of the 1960s (Cutileiro, 1977) and from Carmo’s (2007) critical review of it, this article aims, in the first instance, to draw a parallelism (when analysing the sociodemographic evolution and the distribution of the land in Alentejo and the interior of the Algarve), by articulating the changes registered with the recent migratory influxes, dating from the second decade of the 21st century. Secondly, we will try to examine the profound changes verified in the expectations of the Nepalese immigrant workers interviewed, in connection with the mechanisms underlying the exploitation of their labour. In addition to those, Nepalese and Portuguese recruiters, Portuguese farm owners and farm managers were interviewed – in a total of 38 interviews, conducted both in Portugal and Nepal. Our approach is qualitative and interpretive, drawing on the main themes extracted from the interviews, as well as on a detailed content analysis.